Penerapan Model Pembelajaran Kooperatif Tipe Picture and Picture dalam Meningkatkan Hasil Belajar Tematik Pada Peserta Didik MIN 1 Kendari - Jumiati Jumiati; Erdiyanti Erdiyanti (Diniyah: Jurnal Pendidikan Dasar, 2021)
This study attempts to examine the improvement of thematic learning outcomes of students at MIN 1 Kendari by applying a picture and picture type of cooperative learning model. This study employed classroom action research with 34 participants of class IVc in the first semester of the 2019/2020 academic year. This research was conducted in three cycles with research procedures: planning, implementation, observation, evaluation and reflection. Data collection techniques used observations, interviews, tests, and documentation which were analyzed descriptively qualitative. The results showed that the students' thematic learning outcomes through the application of the picture and picture cooperative learning model increased. The students' learning mastery in the pre-cycle is 14.70% with an average value of 57.64 and after the first cycle of action, learning completeness reaches 47.05% with an average value of 64.11. Then the learning mastery of students in the second cycle reached 64.70% with an average value of 74.11 and in the third cycle, the learning mastery of students reached 94.11% with an average value of 88.52. The percentage increase in student learning outcomes from pre-cycle to cycle III was 93.11%.Keywords: Thematic Learning, Picture and Picture.